DRIVERS AND BARRIERS : A STUDY ON CROSS-BORDER ECOMMERCE TRADE POTENTIAL IN THE RCEP REGION - Lili, Zhang; Muhammad Asraf, Abdullah (The Seybold Report, 2024)
This study aims to evaluate the development levels and trade potential of cross-border e-commerce (CBEC) between China and its Regional Comprehensive Economic Partnership (RCEP) partners. Utilizing the crossborder e-commerce ecosystem theory and Principal Component Analysis (PCA), the research integrates logistics performance, information flow, and digital infrastructure as core explanatory variables within an extended gravity model framework. The study analyzes trade volume data from 2013 to 2022, employing the Generalized Method of Moments (GMM) for model estimation. Key findings indicate that supporting factors, especially logistics performance and information flow, are pivotal in enhancing CBEC development. China maintains a leading position due to its advanced logistics and network infrastructure, whereas countries like Laos lag due to infrastructural and economic disparities. The analysis further reveals that while China's CBEC development level has a limited impact on increasing total trade volumes, the development levels of partner countries significantly enhance their trade volumes with China. Additionally, per capita GDP of partner countries does not significantly influence total trade volumes, though China's per capita GDP positively affects them. Distance costs negatively impact trade volumes at a 10% significance level. Untapped trade potential exists between China and several RCEP partners, including South Korea and Japan, highlighting the need for targeted trade promotion strategies. These findings underscore the critical importance of improving logistics, infrastructure, and digital economy frameworks to maximize CBEC trade potential. Policymakers should focus on reducing trade barriers, enhancing digital infrastructure, and fostering economic cooperation to fully leverage the trade potential within the RCEP framework.